Public relations confidentiality: An analysis of pr practitioner–client privilege in high profile litigation - Myers, Cayce (Public relations review, 2015)
•PR practitioners can claim attorney–client privilege.•PR work done for litigation may be protected under attorney–client privilege.•Federal courts are frequently viewing PR work as a necessity for litigation.•PR practitioners should take steps to protect client confidences during lawsuits. This article explores the legal protection given to confidential information between public relations practitioners and their clients under U.S. law. Increasingly, federal courts have recognized the importance of having a media strategy during high profile litigation. However, courts have a mixed approach for protecting confidential information divulged to PR practitioners during litigation. This article analyzes recent U.S. court decisions extending attorney–client privilege to non-lawyers and provides suggestions on when attorney–client privilege may extend to PR practitioners.